If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(2x+3)+2(9x-5)=4(17-18x)-3(5-9x)
We move all terms to the left:
9(2x+3)+2(9x-5)-(4(17-18x)-3(5-9x))=0
We add all the numbers together, and all the variables
9(2x+3)+2(9x-5)-(4(-18x+17)-3(-9x+5))=0
We multiply parentheses
18x+18x-(4(-18x+17)-3(-9x+5))+27-10=0
We calculate terms in parentheses: -(4(-18x+17)-3(-9x+5)), so:We add all the numbers together, and all the variables
4(-18x+17)-3(-9x+5)
We multiply parentheses
-72x+27x+68-15
We add all the numbers together, and all the variables
-45x+53
Back to the equation:
-(-45x+53)
36x-(-45x+53)+17=0
We get rid of parentheses
36x+45x-53+17=0
We add all the numbers together, and all the variables
81x-36=0
We move all terms containing x to the left, all other terms to the right
81x=36
x=36/81
x=4/9
| 12.5+mm=7.6 | | 5x^2-26x-18=0 | | 3f-7=10f | | -7x+75=x+219 | | 12.6x-2.1x=189 | | 2x²+16x+14-54=0 | | 8x-17=85 | | x2=16 | | 2x²+16x+14=54 | | -6(x+4)+2x+5=7x+6 | | -6=k=-9 | | u=-10+6u | | M=4m+15m-7 | | -14=4(v-5)-2v | | 3x(x-1)=2x-3+3x | | 8+45=a-53 | | 3x^2-7x+16=0 | | 7-2c=-3c | | -x+10=4x-15 | | 3a+10=65 | | x2+9x=0 | | 20n+6=n-374 | | .9=x/36 | | -10g=9-7g | | 1/8-8/9w=1/9w+9/8 | | -4(2x-3)+3x-5=-18 | | (2x-9)=15 | | 9w-6=3w+7 | | .90=x/36 | | -5(x+1)-11=13+6 | | -8+2r-6r=-8r-4r | | a-344=-9a-4 |